2004
DOI: 10.1055/s-2004-835870
|View full text |Cite
|
Sign up to set email alerts
|

Differenzialdiagnose des Polyhydramnions beim Hyperprostaglandin-E-Syndrom: Case-Report

Abstract: If HPS is suspected to be the cause of polyhydramnions, the chloride concentrations in the amniotic fluid and molecular analysis for HPS should be performed. Interdisciplinary care, diagnostics and therapy in an experienced perinatal center are essential for an optimal outcome of the pregnancy and the newborn infant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Of note, polyhydramnios is never seen during the pregnancy that leads to infants bearing AVPR2 or AQP2 mutations. The most common causes of increased amniotic fluid include maternal diabetes mellitus, fetal malformations and chromosomal aberrations, twin-to-twin transfusion syndrome, rhesus incompatibility, and congenital infections (81). Postnatally, polyuria was the leading symptom in 19 of the 32 patients.…”
Section: Complex Polyuro-polydipsic Syndromementioning
confidence: 99%
“…Of note, polyhydramnios is never seen during the pregnancy that leads to infants bearing AVPR2 or AQP2 mutations. The most common causes of increased amniotic fluid include maternal diabetes mellitus, fetal malformations and chromosomal aberrations, twin-to-twin transfusion syndrome, rhesus incompatibility, and congenital infections (81). Postnatally, polyuria was the leading symptom in 19 of the 32 patients.…”
Section: Complex Polyuro-polydipsic Syndromementioning
confidence: 99%
“…While the most common causes of increased amniotic fluid include maternal diabetes mellitus, fetal malformations and chromosomal aberrations, twin-to-twin transfusion syndrome, rhesus incompatibility and congenital infections [18], in these conditions, polyuria usually does not persist after birth. A novel renal cause of polyhydramnios was recently discovered: Laghmani et al reported in 2016 patients with amniotic fluid index from 24 to 100 cms (normal <20 cm) bearing male fetus with a transient form of Bartter's syndrome and bearing MAGED2 mutations [2].…”
Section: "Pure" Vs "Complex" Ndi With Loss Of Water and Electrolytesmentioning
confidence: 99%